2020
DOI: 10.1108/ajim-02-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

Identifying health information needs of senior online communities users: a text mining approach

Abstract: PurposeThe purpose of this study is to identify the health information needs of senior online communities (SOCs) users, which could provide a basis for improving senior health information services.Design/methodology/approachA total of 14,933 health-related posts in the two most popular senior online communities (Yinling and Keai) in China are crawled as a corpus. Based on the results of word frequency analysis, text classification is performed based on two aspects: medical systems (Western medicine and traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Previous studies have mainly focused on online health information behaviour among healthy and young populations (Chen et al, 2017;Ghiasi, 2021;Li et al, 2020;Qian et al, 2019), and some instruments have been developed to evaluate health informationseeking behaviour among these groups of people, such as the Information-seeking Behaviour Scale and Information-seeking Behaviour Scale for Undergraduates (Chen et al, 2021;Timmers & Glas, 2010). However, people with cancer are different from healthy people and young people in terms of having worse physical conditions, older age distribution and higher demand for health and disease information.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Previous studies have mainly focused on online health information behaviour among healthy and young populations (Chen et al, 2017;Ghiasi, 2021;Li et al, 2020;Qian et al, 2019), and some instruments have been developed to evaluate health informationseeking behaviour among these groups of people, such as the Information-seeking Behaviour Scale and Information-seeking Behaviour Scale for Undergraduates (Chen et al, 2021;Timmers & Glas, 2010). However, people with cancer are different from healthy people and young people in terms of having worse physical conditions, older age distribution and higher demand for health and disease information.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Others collected older adults' opinions on how technology could improve their intake (Łukasik et al, 2018) or synthesized literature (Scott et al, 2018;Takemoto et al, 2018). One study evaluated online communities and found posts included concerns about vitamins, fats, and protein (Qian & Gui, 2020).…”
Section: Nutrition Focus Characterizationmentioning
confidence: 99%
“…Like tablet hardware, this popular software is becoming increasingly important. Only one study addressed social media use (Qian & Gui, 2020); however, the new generation of aging adults is social media aware. Social media is a promising area to introduce future older adults to videos, 3D experiences, and new learning.…”
Section: Future Research and Limitationsmentioning
confidence: 99%
“…Therefore, machine learning-based methods such as text mining and topic recognition have gradually become the most common methods to study users' information needs. Qian and Gui [19] applied word frequency analysis to identify the information needs of users in the elderly health community, which is mainly divided into 4 themes: coping with aging, diet and nutrition, physical exercise, and mental health. Based on the coword analysis and the latent Dirichlet allocation topic model, Wang et al [15] found that during the COVID-19 pandemic, Chinese online medical and health community users had the highest demand for information about disease symptoms [15].…”
Section: Introductionmentioning
confidence: 99%